2019
DOI: 10.1016/j.ejrad.2019.108712
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the nuclear medicine personnel occupational exposure to radioiodine

Abstract: DENM) who are occupationally exposed to 131 I. Materials and Methods: The exposure was monitored by whole-body and finger ring dosimeters. The thyroid iodine intake was measured by a whole-body spectrometer equipped with two semiconductor gamma radiation detectors. A cytokinesis-block micronucleus assay and the premature chromosome condensation technique were used to assess the aberration score. Cytogenetic analyses were carried out on a group of 29 workers and were compared to 32 controls (healthy donors), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…4 A). As the years of working with IR increased, so did the frequency of MN, with this result concurring with many studies [ 36 , 37 , 47 49 , 51 , 52 , 54 – 57 ]. Some studies have reported an increase in the frequency of MN as a function of age in medical exposure [ 37 , 51 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…4 A). As the years of working with IR increased, so did the frequency of MN, with this result concurring with many studies [ 36 , 37 , 47 49 , 51 , 52 , 54 – 57 ]. Some studies have reported an increase in the frequency of MN as a function of age in medical exposure [ 37 , 51 ].…”
Section: Discussionsupporting
confidence: 89%
“…As the years of working with IR increased, so did the frequency of MN, with this result concurring with many studies [ 36 , 37 , 47 49 , 51 , 52 , 54 – 57 ]. Some studies have reported an increase in the frequency of MN as a function of age in medical exposure [ 37 , 51 ]. However, in this study, no relationship was observed between age and MN frequency, which is consistent with the reports of some studies [ 45 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…Relatively low activities are admin-that there are not apparent differences in terms of internal radiation hazard due to inhalation of radioiodine I-131 in these categories of medical units. Testing of iodine content in thyroid workers in a Polish nuclear medical hospital was also performed by other authors [14,15]. The results indicate the occurrence of analogous ranges of measured activity in the thyroid gland.…”
Section: Discussionmentioning
confidence: 75%
“…The most exposed area of NM workers is the hands due to the fact that the unsealed source of radiation is relatively close to them at the time of labelling, dispensing and injecting radiopharmaceuticals to patients [2][3][4]. To evaluate extremity doses, passive ring dosimeters are usually used in hospitals [1][2][3][4][5][6], however, published researches [1,[7][8][9] indicate that the dose distribution over the hand is inhomogeneous and the maximum dose is received by fingertips, which means that the dose results obtained with a ring dosimeter in the typical monitoring position (base of the middle finger of the dominant hand) can be much lower.…”
Section: Introductionmentioning
confidence: 99%